Autotranplantasi Caninus Maxilla pada Soket Incisivus Lateral Maxilla menggunakan Anestesi Lokal - Adi Subekti Putra; Maria Gorreti Widyastuti; Poerwati Soetji Rahajoe (Majalah Kedokteran Gigi Indonesia, 2015)
Autotransplantation of Maxillary Canines in Lateral Incisor Socket Using Local Anesthetic. Autotransplantation as the primary option that has many benefits over a period of mixed dentition for contributing to stimulating bone growth; it is not obtained on dental implants. Autotransplantation donor tooth is best when root development reaches half or one-third of the total length with open apex, with a success rate of 94%. However in the complete root, the success rate is lower (84%) due to periodontal issues which are often damaged when making the donor. In this case report, the authors performed the autotransplantation using a whole root donor tooth. Embedded teeth were used to replace deciduous canine teeth with rampant caries. The aim of this case is to replace rampant caries teeth that are not anatomically perfect.